Biodemography - Carey, James R. (Henry Stewart Talks, 2016)
Biodemography of lifespan: concepts, lifespan and sociality, and human lifespan evolution, Population biology of the elderly: role of elderly in nature & emphasis on social species, Experimental biodemography of aging: studies in model organisms
Archived at 2024/04/30